Did the Delamerian Orogeny start in the Neoproterozoic? - Turner, Simon; Haines, Peter; Foster, David; Powell, Roger; Sandiford, Mike; Offler, Robin (University of Chicago Press, 2009)
Recent studies generally have inferred that the onset of convergence in the Delamerian Orogeny in southeastern Australia commenced at the end of the Early Cambrian (~514 Ma) after the deposition of Kanmantoo Group sediments. Correlative sequences in Antarctica provide evidence that convergent deformation (Ross Orogeny) commenced between 580 and 540 Ma, leading to the interpretation that the locus of deformation migrated or jumped northward along the paleo-Pacific margin of Gondwana. However, the absence of upper Neoproterozoic sequences in the southern Adelaide Rift Complex requires either significant pre-Kanmantoo erosion (for which there is no evidence) or a depositional hiatus due to uplift. New Rb-Sr data from solution cleavage in Brachina Formation sedimentary rocks at Hallett Cove, South Australia, date deformation at 554±10 Ma, while ⁴⁰Ar/³⁹Ar data on white mica in the center of the cleavage yield a relatively flat plateau-like segment with an age of 533±15 Ma. Additional evidence for a pre-514-Ma onset of deformation is provided by a 525±7-Ma ⁴⁰Ar/³⁹Ar age for biotite that developed in a mylonite within a Mesoproterozoic granitic gneiss in the Myponga basement inlier to the south of Hallett Cove. Thus, the data imply that convergence commenced more or less synchronously with contraction during the Ross Orogeny in Antarctica. Deposition of the Cambrian Kanmantoo Group therefore occurred in a synorogenic setting analogous to deposition of the upper Byrd Group in Antarctica.